The impact of the Poltava landfill on drinking water and water bodies - Молчанова, А. В. (Scientific Progress & Innovations, 2018)
In Poltava, a landfill for solid waste near the village Makukhovka (4 km from Poltava) is operated. The landfill has no protective screens, and at a distance of 800 m from the landfill the Kolomak River flows. The groundwater contaminated by the filtrate flowing to the Kolomak River is a serious, permanent, multicomponent source of pollution, the effect of which must be eliminated or minimized, because Kolomak flows into Vorskla, which carries its water into the Dnieper. Downstream of the Vorskla River not far from Poltava city are located cities and villages which use surface intake of drinking water. Among them there is a big city Kremenchuk. The results of the influence of the Poltava solid waste landfill on drinking water and water bodies are presented. Solid waste landfills (SWL) are dangerous sources of environmental pollution. Especially those of them that are not equipped with an anti-filtration screen and are operated without proper insulation of inert materials and without the necessary compaction of waste. Environmental and sanitary problems associated with their operation are almost the same, this is a negative impact on all components of the environment, including surface and groundwater. The complexity of this impact is also revealed in the fact that pollution has a multicomponent nature, that is, various substances of a very wide range enter into the environment from the side of solid waste landfills in various ways and the number of pollutant components is constantly increasing.